2015
DOI: 10.1142/s2382626615500070
|View full text |Cite
|
Sign up to set email alerts
|

Slow Decay of Impact in Equity Markets

Abstract: Using a proprietary dataset of meta-orders and prediction signals, and assuming a quasi-linear impact model, we deconvolve market impact from past correlated trades and a predictable return component to elicit the temporal dependence of the market impact of a single daily meta-order, over a ten day horizon in various equity markets. We find that the impact of single meta-orders is to a first approximation universal and slowly decays to zero (or to a small value), possibly as a power-law. We show that auto-corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
47
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 28 publications
(49 reference statements)
13
47
0
Order By: Relevance
“…However, our calculation shows that the empirical determination of the mechanical component of impact should carefully take into account any possible information content of the analyzed trades, as well as the possible auto-correlation of the trades. This parallels the discussion offered in [11,13], where attempts are made to measure the decay of mechanical impact I(Q, t > T ) in equity markets, with the conclusion that the mechanical component of impact seems indeed to relax to zero at large times.…”
Section: Mechanical Vs Informational Impactsupporting
confidence: 56%
See 3 more Smart Citations
“…However, our calculation shows that the empirical determination of the mechanical component of impact should carefully take into account any possible information content of the analyzed trades, as well as the possible auto-correlation of the trades. This parallels the discussion offered in [11,13], where attempts are made to measure the decay of mechanical impact I(Q, t > T ) in equity markets, with the conclusion that the mechanical component of impact seems indeed to relax to zero at large times.…”
Section: Mechanical Vs Informational Impactsupporting
confidence: 56%
“…We have shown that our model is free of price manipulation, which makes it the first consistent, non-linear and time dependent theory of impact. Our setting also suggests how prices can be naturally decomposed into a transient "mechanical impact" component and a permanent "informational" component, as initially proposed by Almgren et al [2], and recently exploited in [11,13] -see Section IX. Let us insist once again that this decomposition allowed us to construct diffusive prices (albeit with a generic short-term mean-reverting contribution).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation (19) indicates that most of the incoming meta-order is executed against the rapid agents for t < t but the slow agents then take over for t > t (see Fig. 4).…”
Section: From Linear To Square-root Impactmentioning
confidence: 99%